In order to protect our mothers, we need to prioritize our nurses and midwives. (2021) - Muller, Anna; Sayenda, Mphatso; Sylvies, Fiona; Rose, Sharon; Baltzell, Kimberly; Mhango, Mercy
Abstract: Aim: To investigate working conditions and experiences of nurses and midwives in a rural district in southern Malawi, a place where nurse-midwives are at the frontlines of maternal care. Methods: Two focus group interviews were conducted with nurses and midwives (N = 20) in March 2018. Interviews were conducted in person, audio-recorded, and transcribed in Word. Themes were developed during hand-coding by a member of the research team and analyzed in a framework table. All documents were kept on a password protected computer with access limited to the first author and one other member of the team. All participants provided both verbal and written consent prior to the interviews. Results: The major theme that emerged from the group interviews was primarily resource challenges; specifically staffing shortages, poor infrastructure, and lack of essential birthing supplies. Conclusions: The findings suggest that without the tools to do their job in a safe working environment, nurses and midwives may leave nursing and midwifery to pursue alternative careers if they cannot provide safe and comprehensive care. While this problem had been identified in other studies, a dedicated effort to remedy such challenges is necessary at the district and national level.